2022
DOI: 10.1186/s12951-022-01318-8
|View full text |Cite
|
Sign up to set email alerts
|

Ceria-Zirconia nanoparticles reduce intracellular globotriaosylceramide accumulation and attenuate kidney injury by enhancing the autophagy flux in cellular and animal models of Fabry disease

Abstract: Background Fabry disease (FD) is a lysosome storage disease (LSD) characterized by significantly reduced intracellular autophagy function. This contributes to the progression of intracellular pathologic signaling and can lead to organ injury. Phospholipid–polyethyleneglycol-capped Ceria-Zirconia antioxidant nanoparticles (PEG-CZNPs) have been reported to enhance autophagy flux. We analyzed whether they suppress globotriaosylceramide (Gb3) accumulation by enhancing autophagy flux and thereby att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…LY294002, as an autophagy inhibitor, inhibits the phosphorylation of AKT through broad-spectrum suppression of PI3K, and final achieves autophagy inhibition [ 35 ]. Some literatures have reported that autophagy retardation could aggravate glomerular diseases, suggesting that increased autophagy may attenuate MN [ 37 , 38 ]. Here, we found that LY294002 could reverse the reduction of mesangial cells proliferation and inflammation after SalB intervention.…”
Section: Discussionmentioning
confidence: 99%
“…LY294002, as an autophagy inhibitor, inhibits the phosphorylation of AKT through broad-spectrum suppression of PI3K, and final achieves autophagy inhibition [ 35 ]. Some literatures have reported that autophagy retardation could aggravate glomerular diseases, suggesting that increased autophagy may attenuate MN [ 37 , 38 ]. Here, we found that LY294002 could reverse the reduction of mesangial cells proliferation and inflammation after SalB intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The PEG–CZNPs were synthesized following a previous report. , Briefly, 5 mL of the CZNPs sample in chloroform (10 mg/mL) was blended with 4 mL of 18:0 PEG2000 PE (contains: chloroform). The majority of the chloroform was then removed using a rotary evaporator, and the sample was incubated at 80 °C for 2 h in a vacuum oven to ensure complete solvent removal.…”
Section: Methodsmentioning
confidence: 99%
“…After cooling, 3 mL of nitric acid and 0.5 mL of hydrofluoric acid were added for a further overnight incubation at 150 °C. The vessel lid was then opened and heated to dryness, followed by adding 10 g of 1% nitric acid solution for ICP-MS measurement …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations